Municipal Bonusing of Industry: The Legislative Framework in Ontorio to 1830 - Bloomfield, Elizabeth (Urban History Review / Revue d'histoire urbaine, 1981)
Many Ontario municipalities between the 1870s and the 1920s tried to influence the pace and form of urban growth by granting inducements to manufacturers. This research note offers a summary of the Ontario legislation relating to such inducements. It defines the forms of assistance municipal councils might grant to industrial enterprises and the restrictions on the powers of municipalities, as these were amended from time to time. The legislative framework of bonusing is considered in four periods: 1867-1892; 1892-1900; 1900-1924; after 1924; and excerpts from the legislation are presented in an appendix. Some implications of bonusing in the study of urban history are suggested.